Beginners in prescribing practice: Experiences and perceptions of nurses and doctors. Issue 5 (15th January 2018) - Lim, Anecita Gigi; North, Nicola; Shaw, John
Abstract : Aims and objectives: To investigate and compare the experiences and perceptions of nurses and doctors in becoming prescribers. Background: The development of core skills, knowledge and attitudes as a prescriber is among the present foci of current medical education, and the requirements for ongoing mentorship, support and education for novice medical prescribers have been identified as important training components. However, little is known of the prescribing practices of other health professionals who are also new to prescribing, for example, nurse prescribers. Design: This qualitative study was guided by a constructivist narrative approach using a multiple case narrative strategy. Methods: A purposive sampling approach was used, with a view to selecting participants to best illuminate the experiences of beginning to prescribe. Individual interviews were conducted, 26 in total, lasting approximately one hour each and were audio‐recorded. Results: Common themes were found across prescribing groups: fear and anxiety when taking on prescribing responsibility; the strategy of using a personal list of medicines to support safe practice; how this list was expanded over time; referring to senior colleagues in prescribing decision‐making. Conclusions: This study shows that the journeys are similar for nurses and doctors as beginning prescribers. The effort required for a novice prescriber to select the most appropriate medication and write prescriptions can be extensive as development of expertise takes time and occurs over months or years. Relevance to clinical practice: Medical and nurse prescribers differ in term of educational preparation, their journeys as beginner prescribers share common behaviour and practices. Clinical experience and mentorship important to enhance skill development in prescribing and should be advocated for all prescribers. Beginner prescribers require ongoing education and support when prescribing for high risk patients or when prescribing new drugs